Nilai Moral dan Patriotisme dalam Novel Senja dan Pagi Karya Alffy Rev dan Linka Angelia - Nabila Zulfa Hakimah; Haerussaleh Haerussaleh; Imayah Imayah (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2023)
It is important to instill a patriotic attitude from an early age, of course it is also balanced with morals. This research is to describe the values, namely morals and patriotism in the novel Senja dan Pagi. This ressearch has the main objectives, namely: (1) describing the moral values that exist in the characters which include religious values, hobnesty, tolerance, responsibility, (2) describing the values of patriotism possessed by the characters which include the values of courage, being eilling to sacrifice for the sake of their nation, not easily give up, and love the country. Using descriptive qualitative research. The technique used for this research is reading and not-taking techniques. The result of the discussion concluded that seventeen data were found. With details of seven data moral values and ten data values of patriotism.